خیبرپختونخوا میں جرائم (رہزنی،ذاتی دشمنیوں اورمنشیات کی تیاری و اسمگلنگ )کی روک تھام میں مفتیان کرام کی خدمات کا تحقیقی تجزیہ: “An Analytical Study of the Services of Muftis in the Prevention of Crime (Robbery, Personal Enmities, and Drug Production and Smuggling) in Khyber Pakhtunkhwa.” (Khairulummah, 2025)
Crime prevention is a multidimensional challenge that requires legal, social, and moral frameworks working together. In Khyber Pakhtunkhwa, crimes such as robbery, drug trafficking, corruption, land disputes, extremism, and social unrest have affected stability over the past decades. Islamic teachings emphasize justice, moral responsibility, and social harmony. Religious scholars and Muftis play a crucial role in guiding society through fatwas, sermons, community mediation, and social awareness. This study analyzes crime patterns in Khyber Pakhtunkhwa and examines the contribution of Muftis in crime prevention. The research concludes that collaboration between religious leadership, state institutions, and civil society can significantly reduce crime and strengthen social stability.
Keywords: Muftis, Prevention , Crime ,Robbery, Personal Enmities, Drug Production , Smuggling